Two new species of the green lacewing subgenus Ankylopteryx Brauer, 1864 (s. str.) (Neuroptera, Chrysopidae) from China - Ma, Yunlong; Liu, Xingyue (Zootaxa, 2021)
Two new species of the green lacewing subgenus Ankylopteryx Brauer are described from southern Yunnan, China, namely Ankylopteryx (A.) diffluens sp. nov. and Ankylopteryx (A.) rubrocincta sp. nov.. An updated key to the species of this subgenus is provided.